Relasi Kuasa dalam Tata Kelola Objek Wisata Pantai Sebanjarar Studi Relasi dalam Pengembangan Objek Wisata Pantai Sebanjar - Siti J.K.S.Oramahi; Syahrin Badrin Kamahi; Boli Tonda Baso (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The management of Sebanjar beach tourism objects is one form of improving the welfare of the community through the provision of supporting facilities and infrastructure. However, this management requires strategic power relations as the main means of managing tourism objects. This study examines the management of tourism objects that are hampered by the lack of power relations between the government and land owners at the location of the tourist attraction. This study seeks to determine and analyze the power relations in the governance of Sebanjar beach tourism objects in Alor Regency. This study aims to reveal the power relations held by the government towards the surrounding community and as land owners. The theory used is the theory of power put forward by Michael Foucault to support researchers in determining and analyzing the power relations of the management of Sebanjar beach tourism objects. Researchers use a qualitative approach with a case study research type. Data collection techniques include observation, interviews, and documentation. The results of this study prove that the management of tourist attractions does not always prosper the community. This is because there is a lack of power from the government as the manager of the Sebanjar beach tourist attraction. In the management process, there is an obstacle because the land owner claims that the land they have built is tribal land, not individual land where the land was donated by a family who has limited human resources and as the land owner asks for management to be carried out in a balanced manner. The conclusion of this study is the lack of power relations by the government towards the landowner community and the local community.